Diseño del proceso de selección del personal por competencias conductuales en el área operativa en el puesto de gerente de estación Atimasa Quito 2021 - Valdez Balcázar, Paola de Jesús (2021)
Designing a staff selection process based on behavioral competencies is a great benefit to the organization, since the results of this process are based on many other results, both for employees and for the organization in general. The selection of personnel represents one of the most important processes within the Talent Management department in Atimasa.